Growth and Development in Kerala : Economic Reforms in Kerala - P D JEROMI (Economic and Political Weekly July 23, 2005, 2005)
Economic reforms in Kerala were at a snail's pace till the fiscal crisis of the state in 2001. Over the past four years, the state government has initiated a number of measures to accelerate economic growth. Taking into consideration mid-2001 to mid-2004 as the first phase of the reform period, this paper examines the impact of reforms on the primary, secondary and tertiary sectors of the economy and the reasons for the failure of some reforms due to the political, social and cultural environment, a lack of consensus, poor implementation and follow-up.